O’zbekistonda yo’q bo’lib borayotgan va yo’q bo’lib ketgan turizm zonalari - Ko'chimov Fazliddin G'afurovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The tourism landscape of Uzbekistan presents a unique phenomenon characterized by the presence of disappearing and reappearing tourism zones. This thesis investigates the dynamics of these zones, examining the factors contributing to their fluctuating accessibility, visibility, and attractiveness. Through a multidisciplinary approach combining geographical analysis, cultural heritage studies, and tourism management perspectives, the study aims to provide insights into the implications of these phenomena for tourism development, conservation efforts, and sustainable practices in Uzbekistan.